1998
DOI: 10.3141/1626-14
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anaerobic/Aerobic Biostimulation for Remediation of Rail Yards Contaminated by Diesel Engine Repair and Maintenance

Abstract: Perchloroethylene (PCE) and trichloroethylene (TCE) have been commonly used in the repair and maintenance of diesel engine locomotives. Improper handling, storage, and disposal lead to contamination of rail yard soils and groundwater with chlorinated ethylenes. Benzene, toluene, ethyl-benzene, and xylene (BTEX) are also common contaminants at rail yards because of the leakage of diesel fuel storage tanks and spills of diesel fuel. Co-contamination of groundwater with BTEX and chlorinated ethylenes allows for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Toluene and TCE co-contaminate sites such as railyards, where toluene enters the soil through fuel spills or storage tank leaks, and TCE through accidental release during its use and disposal by maintenance personnel (Hirl 1998;Sung et al 2003). In other instances of TCE contamination, toluene may be added in order to stimulate cometabolic removal of TCE (McCarty et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Toluene and TCE co-contaminate sites such as railyards, where toluene enters the soil through fuel spills or storage tank leaks, and TCE through accidental release during its use and disposal by maintenance personnel (Hirl 1998;Sung et al 2003). In other instances of TCE contamination, toluene may be added in order to stimulate cometabolic removal of TCE (McCarty et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…At the Savannah River site alone, the DOE estimates there are 4.4 million kg of TCE contaminated soil and groundwater (Hazen, 1991). Hirl (1998) indicated that toluene and trichloroethylene are common cocontaminants at rail yards because of diesel fuel spills and storage tank leakage, in addition to improper handling, storage, and disposal of trichloroethylene used in the maintenance of locomotives.…”
Section: Introductionmentioning
confidence: 99%
“…9 Pseudomonas putida F1 has been demonstrated to have a high capability to metabolize TCE 8,11 in the presence of toluene, which is also one of the co-pollutants with TCE found in contaminated industrial sites. 3,14,15 However, few studies have been conducted regarding P. putida F1 behavior in biofilm reactors, [16][17][18] especially for aqueous-phase TCE treatment, which was done mostly in batch scales. 19,20 The fundamental issues for a sustained aqueous-phase TCE biodegradation via cometabolism are oxygen limitation, competitive inhibition from the growth substrate, and toxic effect 21,22 from the TCE degradation products.…”
mentioning
confidence: 99%